2009
DOI: 10.1097/icu.0b013e32832f7f25
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in retinoblastoma genetic research

Abstract: These and related research efforts reveal novel data that enhance our understanding of the biology of retinoblastoma. These observations may facilitate new therapeutic approaches to further decrease the morbidity and mortality associated with retinoblastoma and other more common forms of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…While there were 18/51 (35%) cases who showed EOE and positivity of PCR for Rb-1 gene mutation and a positive association was seen with EOE and gene mutation (p = 0.005). Our results are consistent with Eagle et al, their harbor mutations in both copies of the RB1 gene and associated with uveal invasion and retrolaminar optic nerve invasion [5,16,17]. Laurie et al proved this association at molecular basis, and their "detailed analysis of these cells as they were propagated in culture from the primary tumor shows that changes in cadherin-mediated cell adhesion are associated with retinoblastoma invasion of the optic nerve prior to metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…While there were 18/51 (35%) cases who showed EOE and positivity of PCR for Rb-1 gene mutation and a positive association was seen with EOE and gene mutation (p = 0.005). Our results are consistent with Eagle et al, their harbor mutations in both copies of the RB1 gene and associated with uveal invasion and retrolaminar optic nerve invasion [5,16,17]. Laurie et al proved this association at molecular basis, and their "detailed analysis of these cells as they were propagated in culture from the primary tumor shows that changes in cadherin-mediated cell adhesion are associated with retinoblastoma invasion of the optic nerve prior to metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…Gains at chromosomal loci 1q32.1, 6p22, and 2p24, encompassing the genes MDM4, E2F3 and DEK, and MYCN respectively, and losses at 16q22 have been described. 5 Recently, Priya and coauthors 6 demonstrated a high frequency of allelic loss in retinoblastoma tumors at a second locus for retinoblastoma: RBL2, which encodes the p130 protein, on 16q12.2. The role of RBL2 is further supported by the findings of Bellan and colleagues 7 pertaining to missing expressions of RBL2/p130 associated with reduced apoptosis and lesser differentiation in human cases of retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 Deletions of 13q14 have extensively been studied in the context of retinoblastoma. 11 On the contrary, proximal deletions affecting the 13q12 region have not been frequently reported. An interstitial 13q12.1q14.1 deletion was reported in a patient with developmental delay, dysmorphic features and hypotonia.…”
Section: Discussionmentioning
confidence: 99%